2016
DOI: 10.1038/cddiscovery.2016.66
|View full text |Cite
|
Sign up to set email alerts
|

FoxO1 interacts with transcription factor EB and differentially regulates mitochondrial uncoupling proteins via autophagy in adipocytes

Abstract: Mitochondrial uncoupling proteins (UCPs) are inducible and play an important role in metabolic and redox homeostasis. Recent studies have suggested that FoxO1 controls mitochondrial biogenesis and morphology, but it remains largely unknown how FoxO1 may regulate mitochondrial UCPs. Here we show that FoxO1 interacted with transcription factor EB (Tfeb), a key regulator of autophagosome and lysosome, and mediated the expression of UCP1, UCP2 and UCP3 differentially via autophagy in adipocytes. UCP1 was down-regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 50 publications
5
31
0
Order By: Relevance
“…Moreover, these mice show increased energy expenditure when fed HFD and maintained under room temperature. These results are in line with the fact that FOXO1 promotes Atgl expression but suppresses Ucp1 transcription (Nakae et al 2008(Nakae et al , 2012Chakrabarti and Kandror 2009b;Chakrabarti et al 2011;Liu et al 2016;Kita et al 2019;Peng et al 2019). Therefore, it appears that at least upon HFD feeding, suppression of Ucp1 expression and energy expenditure would play a dominant role over ATGL-dependent lipolysis.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Moreover, these mice show increased energy expenditure when fed HFD and maintained under room temperature. These results are in line with the fact that FOXO1 promotes Atgl expression but suppresses Ucp1 transcription (Nakae et al 2008(Nakae et al , 2012Chakrabarti and Kandror 2009b;Chakrabarti et al 2011;Liu et al 2016;Kita et al 2019;Peng et al 2019). Therefore, it appears that at least upon HFD feeding, suppression of Ucp1 expression and energy expenditure would play a dominant role over ATGL-dependent lipolysis.…”
Section: Discussionsupporting
confidence: 75%
“…We and others showed that FOXO1 promotes the expression of Atgl (Chakrabarti and Kandror 2009b;Chakrabarti et al 2011;Jung et al 2019). Interestingly, a number of reports showed that FOXO1 suppresses the expression of genes regulating energy dissipation, including UCP1, in white and brown adipocytes (Nakae et al 2008(Nakae et al , 2012Liu et al 2016;Kita et al 2019;Peng et al 2019). However, a recent study indicated that in brown adipose tissue of mice fed ND, FOXO1 does not affect UCP1 and in vitro under specific culture conditions deletion of FOXO1 might even decrease Ucp1 expression in brown adipocytes (Jung et al 2019).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In fact, during white-to-brown conversion stimulated by cold exposure or forskolin treatment (a pharmacological agent that raises intracellular cAMP levels [75]), FoxO1 undergoes inactivation by the co-repressor ZFP238 that, in this way, allows the expression of UCP1 and mitochondrial biogenesis-associated genes [76]. Moreover, FoxO1 activity has been demonstrated to induce autophagy during adipocyte differentiation which has been linked to the downregulation of UCP1 and upregulation of UCP2/3 [77]. This result correlates well with the notion that inhibition of autophagy leads to browning of white adipose tissue, which is manifested by an increased expression of UCP1 [78,79].…”
Section: Foxo1 Involvement In the Browning Phenotypementioning
confidence: 99%
“…In particular, FoxO1 directly binds to the promoter of the transcription factor EB (TFEB), a key regulator of autophagosome and lysosome biogenesis, promoting its transcription during adipocyte differentiation. The use of the FoxO1 antagonist AS1842856 significantly reduced TFEB expression, and thus the induction of autophagy, with consequences on the coordinated expression of UCP1/2/3 during adipocytes differentiation [65,77].…”
Section: Foxo1 Involvement In the Browning Phenotypementioning
confidence: 99%